The Influence of Advertising Media, Brand Ambassadors and Prices on Purchasing Decisions - Saputra, Raihan; Nur'Aeni, Nur'Aeni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Most humans have problems with oily facial skin. Oily facial skin is one of the enemies or also a threat that affects a person's appearance and self-confidence. The presence of facial wash is able to overcome these problems and can reduce pore blockage due to blackheads and acne, rejuvenate facial skin, make facial skin look brighter, fresher, and make you stay young. The mandom coperaton company that produces Gatsby facial wash was established in Indonesia in 1969. The purpose of this research is to test the influence of advertising media, brand ambassadors, and prices on purchase decisions. This research uses quantitative methods. The population used includes Pelita Bangsa University students who have used or purchased Gatsby facial wash products. The number of samples obtained in this study is as many as 76 respondents. The data collection technique carried out in this study uses purposive sampling techniques using primary and secondary data. Data analysis in this study using SmartPLS (Partial Least Square) software. The results of this study show that : 1.) advertising media on purchasing decisions has a positive and significant effect,. 2.) brand ambassador to the purchase decision has a positive and significant effect, then 3.) the price on the purchase decision has a positive and significant effect.